IMPLEMENTATION OF THE CONCEPT OF A SMART UNIVERSITY IN TERMS OF DISTANCE EDUCATION - Ольга Ігорівна Потапчук; Ірина Богданівна Луцик; Ігор Васильович Гевко; Богдан Богданович Буяк (Інформаційні технології і засоби навчання, 2022)
A theoretical analysis of the requirements of modern society for distance education was carried out, which emphasizes the importance of introducing Smart Education. The main functions of Smart Education, which meets the society’s need for open, high-quality distance education, are substantiated. It is noted that Smart Education implements not only basic didactic principles, but also relatively new ones: interactivity, adaptability of learning, flexibility of the educational process. For their implementation, the structure of a Smart course is defined, the development of the components of which is ensured by the use of smart technologies. The needs of the development of the concept of a Smart University are substantiated and its characteristic features are determined. It is established that the implementation of the concept of a Smart University should include scientific research, staffing, educational process, management and marketing of educational institutions, use of modern information technology and digitalization. A strategy has been developed to implement the concept of a Smart University, which is based on the combination of four components "4T": technologies (digital technologies, educational content in free access for students, providing feedback to teachers and students, automation of administrative tasks), tactics (student-centered model, which is based on the appropriate facilities), talents (competent teachers who have a complex of professional competencies, and smart students who are able to develop and improve themselves in the future professional field), traditions (traditions that are supported by modern requirements with prospects for the future). The use of Smart technologies ensures the implementation of the tactics of organizing the activities of a modern university, which is aimed at developing talented students and teachers’ professionalism, taking into account the experience and traditions of classical education. The implementation of the Smart University strategy will help create a modern educational environment and provide access to open distance education.